2020
DOI: 10.36108/laujoces/0202/50(0170)
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Silica on Consolidation and Permeability Properties of Lateritic Soil

Abstract: A reddish-brown lateritic soil obtained from Zaria; Nigeria was treated with up to 2.5% nano-silica. Consolidation properties (i.e. Pre-consolidation pressure, compression index, coefficient of volume compressibility and coefficient of consolidation) of treated specimens were assessed using one dimensional consolidation test. The permeability property of treated soil was also evaluated. The results obtained showed that the pre-consolidation pressure generally increased with increasing percentage of nano-silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The hydraulic conductivity of the soil sample (2.16 × 10 −9 m/s) decreased with increasing CNT and CNF ratio, and the hydraulic conductivity decreased to 9.46 × 10 −10 m/s and 7.44 × 10 −10 m/s with the addition of 0.2% CNT and CNF, respectively [25]. Ochepo and Kanyi treated a lateric soil with nano silica, which has superior properties such as large surface area, small particle size, and porous structure, and showed that the permeability coefficient decreased at pressures above 40 kN/m 2 [26]. Bhadra and Leander investigated the geotechnical properties of fly-ash-doped soils with different nano calcium silicate (NCS) doses (0.2-1%).…”
Section: Introductionmentioning
confidence: 99%
“…The hydraulic conductivity of the soil sample (2.16 × 10 −9 m/s) decreased with increasing CNT and CNF ratio, and the hydraulic conductivity decreased to 9.46 × 10 −10 m/s and 7.44 × 10 −10 m/s with the addition of 0.2% CNT and CNF, respectively [25]. Ochepo and Kanyi treated a lateric soil with nano silica, which has superior properties such as large surface area, small particle size, and porous structure, and showed that the permeability coefficient decreased at pressures above 40 kN/m 2 [26]. Bhadra and Leander investigated the geotechnical properties of fly-ash-doped soils with different nano calcium silicate (NCS) doses (0.2-1%).…”
Section: Introductionmentioning
confidence: 99%